2007
DOI: 10.3354/ame047025
|View full text |Cite
|
Sign up to set email alerts
|

Ecological aspects of viral infection and lysis in the harmful brown tide alga Aureococcus anophagefferens

Abstract: Although many bloom-forming phytoplankton are susceptible to viral lysis, the persistence of blooms of algal species that are susceptible to viral infection suggests that mechanisms prohibiting or minimizing viral infection and lysis are common. We describe the isolation of viruses capable of lysing the harmful brown tide pelagophyte Aureococcus anophagefferens and an investigation of factors which influence the susceptibility of A. anophagefferens cells to viral lysis. Nine strains of A. anophagefferens-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 63 publications
(65 reference statements)
3
47
0
Order By: Relevance
“…Collectively, these findings suggest that early reports and images of phage-like viruses infecting Aureococcus (Milligan and Cosper, 1994) were actually bacterial viruses infecting bacteria in the non-axenic cultures. Isolated Aureococcus viruses infect only a portion of brown tide strains examined (9 of 19; Gobler et al, 2007), suggesting that viruses may impact both bloom diversity and biomass. Cultured viruses isolated from NY coastal waters significantly reduced bloom densities of Aureococcus during short term bottle incubation experiments, suggesting that field populations are also susceptible to viral infection .…”
Section: Sources Of Cell Mortalitymentioning
confidence: 95%
See 1 more Smart Citation
“…Collectively, these findings suggest that early reports and images of phage-like viruses infecting Aureococcus (Milligan and Cosper, 1994) were actually bacterial viruses infecting bacteria in the non-axenic cultures. Isolated Aureococcus viruses infect only a portion of brown tide strains examined (9 of 19; Gobler et al, 2007), suggesting that viruses may impact both bloom diversity and biomass. Cultured viruses isolated from NY coastal waters significantly reduced bloom densities of Aureococcus during short term bottle incubation experiments, suggesting that field populations are also susceptible to viral infection .…”
Section: Sources Of Cell Mortalitymentioning
confidence: 95%
“…Viral densities during Aureococcus blooms are generally elevated compared to most estuarine environments (Gobler et al, 2004a) and field studies have observed a high percentage ($40%) of virally infected Aureococcus cells at the end of blooms, suggesting that viruses may be an important source of mortality during bloom termination (Gastrich et al, 2004). Aureococcus-specific viruses capable of completely lysing brown tide cultures have been isolated from bloom waters in Long Island estuaries (Milligan and Cosper, 1994;Gobler et al, 2007;Rowe et al, 2008). Axenic cultures of Aureococcus infected with field-isolated viruses have been shown to host large (140 nm) icosahedral viruses with morphologies consistent with Phycodnaviridae although contaminating bacterial phages were also found in some viral concentrates isolated from the field (Rowe et al, 2008).…”
Section: Sources Of Cell Mortalitymentioning
confidence: 98%
“…Their high abundance and obligately parasitic lifestyle allow viruses to exert top-down control of cellular organism populations, which is illustrated most dramatically through the implication that viruses are involved in the termination of some algal blooms (e.g., Bratbak et al, 1993;Tarutani et al, 2000;Wilson et al, 2002;Brussaard et al, 2005: Gobler et al, 2007Tomaru et al, 2007). More subtly, viruses contribute to the mortality of bacteria, phytoplankton and higher trophic levels of the aquatic food web (Proctor and Fuhrman, 1990;Suttle, 1994;Baudoux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance can result from subtle modifications of a particular receptor site or from internal metabolic modifications (Lenski, 1988) and can readily develop in laboratory bacterial cultures (Lenski, 1988;Bohannan & Lenski, 1997) and in coastal algal species (Gobler et al, 2007). We originally hypothesized that if the resistant strain, PWH3a-R, still possessed a surface receptor capable of viral adsorption, but not infection, exposure to PWH3a-R cells at 0°C would cause a reduction in the infective titers.…”
Section: Discussionmentioning
confidence: 99%